Macrophage scavenger receptors: Tumor support and tumor inhibition - Kazakova, Elena; Iamshchikov, Pavel; Larionova, Irina V.; Kzhyshkowska, Julia G. (Frontiers in oncology)
Tumor-associated macrophages (TAMs) are a heterogeneous population of myeloid cells that constitute up to 50% of the cell mass of human tumors. TAMs interact with the components of the tumor microenvironment (TME) by using scavenger receptors (SRs), a large superfamily of multifunctional receptors that recognize, internalize and transport to the endosomal/lysosomal pathway apoptotic cells, cytokines, matrix molecules, lipid modified lipoproteins and other unwanted-self ligands. In our review, we summarized state-of-the art for the role of macrophage scavenger receptors in tumor development and their significance as cancer biomarkers. In this review we focused on functional activity of TAM-expressing SRs in animal models and in patients, and summarized the data for different human cancer types about the prognostic significance of TAM-expressed SRs. We discussed the role of SRs in the regulation of cancer cell biology, cell-cell and cell-matrix interaction in TME, immune status in TME, angiogenesis, and intratumoral metabolism. Targeting of tumor-promoting SRs can be a promising therapeutic approach in anti-cancer therapy. In our review we provide evidence for both tumor supporting and tumor inhibiting functions of scavenger receptors expressed on TAMs. We focused on the key differences in the prognostic and functional roles of SRs that are specific for cancer types. We highlighted perspectives for inhibition of tumor-promoting SRs in anti-cancer therapy.